2001
DOI: 10.1039/b102545g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the content and identity of lidocaine solutions with UV–visible spectroscopy and multivariate calibration

Abstract: A method is proposed for the determination of the content and identity of the active compound in pharmaceutical solutions by means of ultraviolet-visible (UV-Vis) spectroscopy, orthogonal signal correction (OSC) and multivariate calibration with soft independent modelling of class analogy (SIMCA) classification and partial least squares (PLS) regression. The content was determined with PLS regression and the identity with PLS regression and SIMCA classification. The method was tested on the local anaesthetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…On the other hand, chemometric applications to improve information obtained from modern instrumental data (i.e. spectral and electrochemical data) in different fields have acquired a routine character [12][13][14][15][16][17][18][19][20][21][22]. Partial least-squares (PLS) has become a usual tool for multivariate calibration because of the quality of the obtained calibration models, the ease of its implementation and the availability of software [23,24].…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…On the other hand, chemometric applications to improve information obtained from modern instrumental data (i.e. spectral and electrochemical data) in different fields have acquired a routine character [12][13][14][15][16][17][18][19][20][21][22]. Partial least-squares (PLS) has become a usual tool for multivariate calibration because of the quality of the obtained calibration models, the ease of its implementation and the availability of software [23,24].…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
“…Figure 9 a,b show the absorbance obtained in the case of the membranes studied compared to the standard of the active substance. Av and L were visible in all membranes having the maximum absorbance for L at 266 nm and membranes with Av content at 288 nm [ 38 , 39 ]. Following the analysis by UV-Vis spectroscopy, the presence of the active substance in the synthesized membranes is observed in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…They had an overlapping spectrum (shown in Figure 2), which informed that not possible determined by univariate analysis. Wiberg et al [ 27 ] reported that the uninformative shape of UV-vis absorption spectra was possible with multivariate data analysis to obtain good results for both quantitative and qualitative determinations.…”
Section: Ultraviolet-visible Spectroscopic Analysismentioning
confidence: 99%
“…Although inductively coupled plasmaoptical emission spectrometry (ICP-OES) is quite good in determining the REEs [ 24 , 25 , 26]; however, it is timeconsuming and expensive. On the other hand, modern automatic analysis methods provide opportunities to collect large amounts of data very easily and are considered valuable and promising ones due to their fast, robustness, cost-effectiveness [ 27 ]. Thus, developing an analysis method for the determination of the REEs based on the modern automatic analysis is desirable.…”
Section: Introductionmentioning
confidence: 99%